The agency of object: the doppa as a narrator for a dynamic Uyghur identity. - Amerasinghe, Shalini (Central Asian Survey, 2026)
This article explores the Uyghur doppa from the late nineteenth and early twentieth centuries to understand Uyghur cultural life and identity. It links the doppa to Uyghur history and the evolving sense of 'Uyghurness', reflecting its cultural significance today, both in Xinjiang and through the diaspora. The limited scholarly work on the doppa, spanning 150 years, suggests a gender bias in documenting female-associated crafts. Ironically, at a time when the doppa holds increasing importance, especially with the creation of Doppa Day (5 May), this lack of resources opens up space for creative discourse on Uyghur identity. The study also reveals a tendency to adapt through cultural experiences while maintaining a deep connection to the homeland. Ultimately, this research demonstrates how a small cultural object can provide profound insights into community sensibilities and material culture.